A Targeted In-Fusion Expression System for Recombinant Protein Production in Bombyx mori - Li, Zhiqian; You, Lang; Zhang, Qichao; Yu, Ye; Tan, Anjiang (Frontiers in Genetics, 2022)
The domesticated silkworm, Bombyx mori, is an economically important insect that synthesizes large amounts of silk proteins in its silk gland to make cocoons. In recent years, germline transformation strategies advanced the bioengineering of the silk gland as an ideal bioreactor for mass production of recombinant proteins. However, the yield of exogenous proteins varied largely due to the random insertion and gene drift caused by canonical transposon-based transformation, calling for site-specific and stable expression systems. In the current study, we established a targeted in-fusion expression system by using the transcription activator-like effector nuclease (TALEN)-mediated targeted insertion to target genomic locus of sericin, one of the major silk proteins. We successfully generated chimeric Sericin1-EGFP (Ser-2A-EGFP) transformant, producing up to 3.1% (w/w) of EGFP protein in the cocoon shell. With this strategy, we further expressed the medically important human epidermal growth factor (hEGF) and the protein yield in both middle silk glands, and cocoon shells reached to more than 15-fold higher than the canonical piggyBac-based transgenesis. This natural Sericin1 expression system provides a new strategy for producing recombinant proteins by using the silkworm silk gland as the bioreactor.